Genetic risk factors for venous thrombosis in the elderly in a case–control study. (26th August 2016) - Karasu, A.; Engbers, M. J.; Cushman, M.; Rosendaal, F. R.; van Hylckama Vlieg, A.
Abstract : Essentials Risk of venous thrombosis (VT) related to common genetic variants in those aged 70+ is unknown. We studied Factor V Leiden, prothrombin mutation, non‐O blood group and family history (FH) of VT. Risk of VT was increased 2.2‐, 1.4‐, 1.3‐ and 2.1‐fold respectively. FH is easy to obtain and can be implemented in clinical decision rules of VT risk in the elderly. Click to hear Prof. Reitsma discuss genetic risk factors of arterial and venous thrombosis Summary: Background: As the incidence of venous thrombosis (VT) increases steeply with age and the number of elderly people is on the rise, studies of VT in this age group are important. Objectives: We aimed to study the associations of common genetic risk factors (i.e. the factor V Leiden and prothrombin G20210A mutations, non‐O blood group and family history of VT) with risk of a first VT in older age (> 70 years). Methods: Four hundred and one consecutive cases with a first‐time thrombosis and 431 controls (all ≥ 70 years) were included in the AT‐AGE case–control study. Information on risk factors for VT, including family history of VT in first‐degree relatives, was obtained by interview. Unprovoked VT was defined as thrombosis not related to surgery, fracture, plaster cast or immobility within 3 months prior to VT. Results: The risk of VT was 2.2‐fold increased in factor V Leiden carriers (95% confidence interval [CI], 1.2–3.9), 1.4‐fold increased in prothrombin mutation carriers (95% CI, 0.5–3.9), and 1.3‐fold increased in those with non‐O blood group (95% CI, 1.0–1.8). Positive family history of VT was associated with a 2.1‐fold increased risk of VT (95% CI, 1.5–3.1). The highest risk of VT was found in individuals who had both a positive family history and were carriers of one of the two prothrombotic mutations. Conclusions: Genetic factors clearly related to VT in younger populations were also risk factors in older age and a positive family history was also important in this age group.